The role of atopy patch test in diagnosis of food allergy in atopic eczema/dermatitis syndrom in patients over 14 years of age - Čelakovská, Jarmila; Vaněčková, Jaroslava; Ettlerová, Květuše; Ettler, Karel; Bukač, Josef (Acta Medica, 2010)
Few studies concerning the importance of food allergy in adolescents and adult patients with atopic eczema exist. The atopy patch tests with food have mostly been studied in infants and children since food allergy plays a role especially in this age group. Aim: The evaluation of the contribution of atopy patch tests in the diagnostic work-up of food allergy (to wheat, cow milk, peanuts, soya and eggs) in the patients with atopic eczema older than 14 years of age. Method: 120 patients were examined in the study in the diagnostic work-up of food allergy – 86 women and 34 men, the mean age 26.5 (s.d. 9.8) and the median SCORAD at the beginning of the study 32.9 (s.d. 14.0). Complete dermatological and allergological examinations in the diagnostic work-up of food allergy were performed (assessment of personal history, assessment of serum specific IgE, skin prick tests, atopy patch tests, diagnostic hypoallergenic diet, food challenge tests with egg, soy, wheat, cow milk and double – blind, placebo – controlled food challenge test with cow milk and wheat. The results of atopy patch tests were compared with the results of other diagnostic methods in the diagnosis of food allergy. Results: The food allergy to cow milk and wheat was confirmed in double – blind, placebo controlled food challenge test in few patients in our study (4 %). The suspicion of food allergy to egg is in 8 %, to peanuts in 13 % and to soya in 4 % of patients in our study. The assessment of atopy patch tests response seems to be of great importance. The reaction in atopy patch tests with more papules has the greatest diagnostic accuracy for predicting the result of challenge tests. At the beginning and at the end of diagnostic hypoallergenic diet the severity of atopic eczema/dermatitis syndrome was recorded in all patients enrolled in the study by evaluating SCORAD. The decrease of SCORAD was statistically important. Conclusion: Atopy patch tests alone cannot be used as a single test for the determination of food allergy in patients with atopic eczema/dermatitis syndrome but such a test, together with other diagnostic methods, can help to trace the food allergy.
Keywords: dospělí; potravinová alergie; Food allergy; Humans; Atopic eczema/dermatitis syndrome; Atopy patch tests; Open exposure test; Double – blind placebo – controlled food challenge tests; mladý dospělý; Dermatitis, Atopic; mužské pohlaví; náplasťové testy; Adult; Adolescent; Food Hypersensitivity; ženské pohlaví; atopická dermatitida; lidé; mladiství; Patch Tests; Male; Young Adult; Female